Matching Students to Augmentative and Alternative Communication: A Single Case Study - DiMeo, Sarah; Baxter, Mary Frances; Zapf, Susan; Pemberton, Jane; Amerih, Husny (Journal of the American Academy of Special Education Professionals, 2018)
The purpose of this case study was to examine if the Matching Assistive Technology to Child Augmentative Communication Evaluation Simplified (MATCH-ACES) assessment can help a special education team select an augmentative and alternative communication (AAC) intervention for a student with special needs. Additionally, this study identified the relative contributions of other interventions that the student received to begin to understand the impact that AAC had on the student. This study was a single case study and used a pretest-posttest design. There was a relationship between using the MATCH-ACES and the student’s individualized education goal improvement. Personal assistance, support from related services, and AAC device use significantly contributed to the student’s goal improvement. Future research should address using the MATCH-ACES assessment tool with a larger sample of students and examine the significance of the contributions of other interventions to confirm and identify critical supports for students with special needs.